(untitled) (Filološke pripombe, 2021)
In this paper, we refer to a polemic from 1898 in which the teacher Evtimica Jancheva from the town of Voden took part. The polemic developed as a response to two texts in which the authors criticised women, especially teachers, for their attitude towards fashion and work. Jancheva’s extensive text, published in the newspaper Novini, in the section Correspondence, defends the right of women to be teachers, to follow the latest fashion trends, etc. In this way, the article by Evtimica Jancheva is the first registered polemical writing in Macedonian literature, in which a woman had taken part, while Evtimca Jancheva is considered to be the first Macedonian woman to take part in a public polemic.